2015
DOI: 10.1016/j.jtcvs.2015.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Does preoperative carotid stenosis screening reduce perioperative stroke in patients undergoing coronary artery bypass grafting?

Abstract: A number of institutions routinely perform carotid artery ultrasound screening before coronary artery bypass grafting (CABG) to identify carotid artery disease requiring revascularization before or during CABG, with the expectation of reducing perioperative neurologic events. The assumptions are that carotid disease is causally related to perioperative stroke and that prophylactic carotid revascularization decreases the risk of post-CABG neurologic events. Although carotid artery stenosis is a known risk facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(58 citation statements)
references
References 100 publications
2
50
0
3
Order By: Relevance
“…314 Therefore, indications for preoperative carotid bifurcation screening by duplex ultrasound are limited. 315 Also, there is no evidence that prophylactic revascularization of unilateral asymptomatic carotid stenoses in CABG candidates reduces the risk of perioperative stroke. It may be reasonable to restrict prophylactic carotid revascularization to patients at highest risk of postoperative stroke, i.e.…”
Section: Prevention Of Stroke Associated With Carotid Artery Disease mentioning
confidence: 99%
“…314 Therefore, indications for preoperative carotid bifurcation screening by duplex ultrasound are limited. 315 Also, there is no evidence that prophylactic revascularization of unilateral asymptomatic carotid stenoses in CABG candidates reduces the risk of perioperative stroke. It may be reasonable to restrict prophylactic carotid revascularization to patients at highest risk of postoperative stroke, i.e.…”
Section: Prevention Of Stroke Associated With Carotid Artery Disease mentioning
confidence: 99%
“…33 Atherosclerosis in cervical and cerebral arteries is the other important etiopathogenetic factor of stroke in patients undergoing cardiac surgery. 34 Studies have identified carotid-artery stenosis as a risk factor for perioperative stroke. [35][36][37][38][39] Anticoagulation, turbulent blood flow, and hypertension during CABG could be responsible for an increased intraoperative risk of intraplaque hemorrhage and subsequent distal embolization.…”
Section: Discussionmentioning
confidence: 99%
“…[35][36][37][38][39] Anticoagulation, turbulent blood flow, and hypertension during CABG could be responsible for an increased intraoperative risk of intraplaque hemorrhage and subsequent distal embolization. 34 Impaired cerebral hemodynamic function distal to carotid-artery stenosis is another determinant of postoperative stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Udar mózgu po CABG ma wieloczynnikową etiologię, która obejmuje zatorowość materiałem z aorty podczas manipulacji, kaniulacji/dekaniulacji oraz zespalania pomostów z aortą wstępującą, agregację płytek podczas stosowania krążenia pozaustrojowego i w stanach nadkrzepliwości, embolizację materiałem z tętnic szyjnych, AF w okresie pooperacyjnym oraz niestabilność hemodynamiczną, zwłaszcza u pacjentów z upośledzoną rezerwą naczyniową mózgu [346].…”
Section: W Badaniu Aggressive Detection and Management Of The Extensiunclassified